The contribution of riparian vegetation to the species composition of the Jonkershoek Valley in Stellenbosch, South Africa - Salie, K. (Khalid) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.